Improving persistence of underrepresented racial minority science majors: where to begin - Oyelaran, Oyindasola (Frontiers in Education, 2023)
Many colleges and universities are interested in implementing effective strategies to support broaden participation and persistence of undergraduates, and especially underrepresented students, in Science, Technology, Engineering, and Mathematics (STEM) majors. While there are programs and models that have proven successful in this arena, many of these models are extremely resource intensive. This Perspective provides a distillation of key aspects of successful programs that institutions could consider implementing as a starting point when thinking about how to design programs to support students in STEM.